ORTHOSIS USAGE IN ORTHOPAEDIC TRAUMA COMPLICATIONS - Abu Hassan, Salmah Anim (International Journal of Allied Health Sciences, 2021)
Orthoses and sometimes prostheses are an important consideration after the extensive injuries suffered in major trauma. An orthosis by definition is an appliance that provides support, protection and affords correction of deformity of a body part. In major trauma appropriate orthotic prescription in early till subacute phase of injury prevents deformities and aids tremendously in functional recovery. Prostheses replace the function a lost limb or appendage when amputations become a choice of management. Orthotic and prosthetic prescription can play a major role in trauma rehabilitation to improve quality of life.